NEW CONCEPT FROM THE PAST: GREEN (ECO) ENTREPRENEURSHİP (Third Sector Social Economic Review, 2017)
In recent years, environment and environmental matters are seemed much more significant than before by the entrepreneurs and researchers. Todays, petroleum and solid fuels’ usage has gradually decreased due to the environmental damages. Instead of all these harmful and uneconomic factors, now cleaner and less harmful even completely harmless solutions are found and renewable energy sources come into prominence in general to be able to protect green and environment. The demand and attention of entrepreneurs for these types of sources and solutions are gradually increased each passing day. By this means, a new type of entrepreneurship has shaped which is called as green entrepreneurship and attracted attention by several entrepreneurs.Green entrepreneurship is one of the factors which will help to prevent environmental deterioration. Green entrepreneurs consider the environment as an opportunity for themselves and engage in environmental activities on the purpose of public welfare. In today’s changing world, green entrepreneurs and green activities have an important place for cleaner and greener world. In this study, definitions related to green entrepreneurship are provided, the importance of green entrepreneurship is emphasized, in addition to this, impeding and influencing factors of green entrepreneurship are discoursed.
Keywords: Environment; Entrepreneur; Entrepreneurship; Green Entrepreneurship; Ecopreneurship